Analysis of Atmospheric Conditions during Air Pollution Episodes in Ankara, Turkey - Sahin, M.; Incecik, S.; Topcu, S.; Yildirim, A. (Informa UK Limited, 2001)
This paper presents a detailed analysis of the meteorological conditions that are associated with strong air pollution episodes in Ankara, Turkey. Based on climatological and air quality data [SO2 and TSP (total suspended particulates)] obtained for the winter months during 1989-1994, the analysis showed that the presence of weak atmospheric pressure gradients and warm air advection were the most important factors leading to high SO2 and TSP concentrations. In addition, the onset of the high air pollution episodes was generally associated with a trend toward negative vorticity at the 850-hPa level.
Keywords: Air Movements; Air Pollutants; Meteorological Concepts; Turkey; Reference Values; Cities; Environmental Monitoring; Forecasting